ADOPTION OF E-PAYMENT TO SUPPORT SMALL MEDIUM ENTERPRISE PAYMENT SYSTEM: A CONCEPTUALISED MODEL - Pauline Xena; Raden Aswin Rahadi (International Journal of Accounting, Finance and Business, 2019)
Payment of transactions towards a cashless society is a trend that cannot be avoided. All these things can happen because of cooperation, trust and human desire to be more practical from the community. Through this study, the researcher gets a new model from author analysis based on 23 previous literature synthesis and find out six independent variables that espouse adoption of e-payment to support small-medium enterprise payment system, that are performance expectancy, culture, acceptance of technology, social influence, security, and effort expectancy. The result of this study would be useful to understand about the adoption of e-payment to support the small-medium enterprise payment system.